Cyber Dating Abuse Victimization and Experiential Avoidance Among Chinese Female Adolescents: The Roles of Self-Compassion and Interpersonal Flexibility - Wang, Hongxia (Journal of interpersonal violence, 2023)
Cyber dating abuse victimization (CDAV) among female adolescents is common and harmful; however, little is known regarding how CDAV relates to victims’ experiential avoidance in the Chinese context. Drawing from general strain theory, this cross-sectional study investigated possible differences in the relationships among CDAV, experiential avoidance, and self-compassion according to female adolescents’ levels of interpersonal flexibility (low vs. high). A sample of 420 female adolescents aged 13 to 17 years (mean age = 15.78 years) who had been in intimate relationships during the past year participated in a voluntary and anonymous paper-and-pencil survey. Participants completed four self-reported measures on CDAV experience, self-compassion, experiential avoidance, and interpersonal flexibility. The findings indicated that nearly 49% of participants had experienced CDAV in the last year; CDAV exposure was directly linked with experiential avoidance and indirectly related to experiential avoidance through self-compassion. Moderation analyses showed that the negative associations between CDAV and experiential avoidance and self-compassion were only significant among participants with low interpersonal flexibility. These findings deepen the understanding of CDAV as a risk factor for reduced self-compassion and increased experiential avoidance in female adolescents. However, high interpersonal flexibility is a potential protector. This study has implications for the prevention of experiential avoidance among female adolescents exposed to CDAV and supports incorporating self-compassion and interpersonal flexibility skills to combat the negative outcomes of CDAV.